2019
DOI: 10.3390/ijms20020296
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Omics and Statistical Learning Integration for the Discovery and Validation of Novel Diagnostic Signatures in Colorectal Cancer

Abstract: The advancement of bioinformatics and machine learning has facilitated the discovery and validation of omics-based biomarkers. This study employed a novel approach combining multi-platform transcriptomics and cutting-edge algorithms to introduce novel signatures for accurate diagnosis of colorectal cancer (CRC). Different random forests (RF)-based feature selection methods including the area under the curve (AUC)-RF, Boruta, and Vita were used and the diagnostic performance of the proposed biosignatures was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…It is a representative ensemble-based machine learning technique that improves prediction accuracy and stability by using multiple decision trees. Even though it is known that the prediction performance of RF is higher than that of decision tree [ 20 ], prediction studies using biomarkers [ 21 ] and those using images [ 22 ] have been mainly conducted for evaluating diseases so far. Moreover, only a few RF-based studies utilize sociodemographic factors, questionnaire data such as health habits, or neuropsychological examination data [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a representative ensemble-based machine learning technique that improves prediction accuracy and stability by using multiple decision trees. Even though it is known that the prediction performance of RF is higher than that of decision tree [ 20 ], prediction studies using biomarkers [ 21 ] and those using images [ 22 ] have been mainly conducted for evaluating diseases so far. Moreover, only a few RF-based studies utilize sociodemographic factors, questionnaire data such as health habits, or neuropsychological examination data [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…But et al, in an interesting study conducted on 4063 incident cases of CRC and 4063 matched controls, reported a significant association between VacA positivity and increased risk of CRC (OR 1.11: CI 95%: 1.01‐1.22), which was stronger in Afro‐Americans (OR 1.45: CI 95%: 1.08‐1.95) . Finally, Long et al, in a sophisticated study employing a novel approach combining multi‐platform transcriptomics and cutting‐edge algorithms in CRC, reported that H pylori may increase the expression of specific signaling biomarkers in epithelial cells …”
Section: Inflammatory Bowel Disease and Colorectal Cancermentioning
confidence: 99%
“…MetSyn afflicts more than 30 percent of adults (>47 million Americans) and is associated with impaired lung function [ 2 , 3 ]. Our group has focused on defining the development of World Trade Center-particulate matter (WTC-PM) associated lung disease in the context of MetSyn in the well-phenotyped Fire Department of New York (FDNY) Cohort [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although one major contributor to poor lung mechanics is from mechanical load-induced stress secondary to abdominal obesity, our prior work shows near equivalent contribution from dyslipidemia in those with WTC-LI [ 2 , 10 , 11 ]. Inflammatory profiles from serum samples collected within three months of 9/11 showed that dyslipidemia predicted WTC-LI even after adjusting for body mass index (BMI), and was in fact a stronger predictor than obesity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 15 , 20 , 21 ]. In light of these findings, we focused our work on the inflammatory effects of lipids in the development of particulate matter (PM)-induced lung injury [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation